Management of Persistent Angina After Myocardial Infarction Treated With Percutaneous Coronary Intervention: Insights From the TRANSLATE‐ACS Study. Issue 10 (24th October 2017) - Fanaroff, Alexander C.; Kaltenbach, Lisa A.; Peterson, Eric D.; Hess, Connie N.; Cohen, David J.; Fonarow, Gregg C.; Wang, Tracy Y.
Abstract : Background: Angina has important implications for patients' quality of life and healthcare utilization. Angina management after acute myocardial infarction (MI) treated with percutaneous coronary intervention (PCI) is unknown. Methods and Results: TRANSLATE‐ACS (Treatment With Adenosine Diphosphate Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events After Acute Coronary Syndrome) was a longitudinal study of MI patients treated with percutaneous coronary intervention at 233 US hospitals from 2010 to 2012. Among patients with self‐reported angina at 6 weeks post‐MI, we described patterns of angina and antianginal medication use through 1 year postdischarge. Of 10 870 percutaneous coronary intervention–treated MI patients, 3190 (29.3%) reported angina symptoms at 6 weeks post‐MI; of these, 658 (20.6%) had daily/weekly angina while 2532 (79.4%) had monthly angina. Among patients with 6‐week angina, 2936 (92.0%) received β‐blockers during the 1 year post‐MI, yet only 743 (23.3%) were treated with other antianginal medications. At 1 year, 1056 patients (33.1%) with 6‐week angina reported persistent angina symptoms. Of these, only 31.2% had been prescribed non–β‐blocker antianginal medications at any time in the past year. Among patients undergoing revascularization during follow‐up, only 25.9% were on ≥1 non–β‐blocker anti‐anginal medication at the time of the procedure. Conclusions: Angina is present in one third of percutaneous coronary intervention–treated MI patients as early as 6 weeks after discharge, and many of these patients have persistent angina at 1 year. Non–β‐blocker antianginal medications are infrequently used in these patients, even among those with persistent angina and those undergoing revascularization.